Prenatal diagnosis and the rcog standards for amniocentesis and chorionic villus sampling 2010: a 5 year review from a single unit. (7th June 2011) - Weston, N; Baker, J; Finn, J; Churchill, D
Abstract : Changes to the Down's syndrome screening programme, aim to increase detection rates and reducing invasive testing. The updated RCOG standards have an impact for units and operators performing prenatal testing. We audited 5 years data, evaluating the unit's and operator performance. The unit has four consultants performing either amniocentesis and/or CVS. 501 procedures were identified between November 2005 and December 2010. Missing data was provided from regional systems. Outcomes were missing from eight cases in the amniocentesis group. Follow-up was complete for 98.4% of pregnancies. Total pregnancy loss rate was 1.0%. Correcting for congenital anomalies and obstetric causes, the perinatal related loss rate was (0.39%)=1 spontaneous abortion and 1 NND. For spontaneous abortion (procedure related) the rate was 0.24%. Overall our figures performed well against the RCOG standards. Replicating these data in other units will encourage updating of the risk assessment for amniocentesis and advice to women.